1,4-Naphthoquinone Derivative as Efficient Photolabile Molecule: Concise Synthesis and Photorelease of Various Functional Compounds - Liu, HaiYing; Suzuki, Mikiya; Kakiuchi, Kiyomi; Kawai, Tsuyoshi; Morimoto, Tsumoru (Synthesis, 2022)
We report on a series of 1,4-naphthoquinone (NQ)-based photolabile molecules, including various functional compounds to be released under light irradiation. They were efficiently prepared from a common precursor for a photoremovable masking group, by attaching different functional compounds such as alcohols, amines, and acids by a concise synthetic method. Synthesis of the common precursor was optimized for two-step reactions and also for a one-pot reaction involving a 1,4-addition and successive aldol reaction from NQ. The functional compounds, such as alcohols, amines and carboxylic, phosphoric, and sulfonic acids, were masked with the NQ-based precursor and were successfully released by irradiation with UV light (λ = 360 nm) in high yields (>90%).
Keywords: photolabile molecules; photoremovable groups; 1,4-naphthoquinone; 1,4-addition; aldol reaction; photorelease